Pengembangan Kemandirian Nelayan Melalui Penerapan Teknologi Mesin Es Balok Menuju Ketahanan Ekonomi - Fadli Afriandi; Syurkarni Ali; Ligar Abdillah; Andika Rahmad Rangkuti; Rizal Maulana Fiqri (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2025)
Traditional fishermen who are members of the Joint Business Group (KUB) of Nelayan Maju Bersama experience obstacles to access the availability of ice blocks. Ice blocks for KUB are an important element in fish preservation to maintain the quality of the catch, the value of the selling price, and the welfare of KUB members. This service activity aims to provide and apply ice block machine technology that has an impact on strengthening the independence of members so that economic resilience is realized. The method used is participatory through the stages of preparation, installation, testing, operation, and evaluation by actively involving partners. The results of the service have shown that the application of ice block machine technology has become a self-sufficient KUB for raw materials for preservation and is able to maintain the quality of fish catches. The evaluation also showed that KUB members showed a high level of satisfaction with the presence of ice block machines in their group. This program also has an impact on improving KUB management in terms of more transparent and accountable governance. So, with this activity, KUB is strengthened to become more independent and economic resilience is realized.